The Efficacy of Zinc Phthalocyanine Nanoconjugate on Melanoma Cells Grown as Three-Dimensional Multicellular Tumour Spheroids - Nkune Williams Nkune; Heidi Abrahamse (MDPI AG, 2023)
Melanoma remains a major public health concern that is highly resistant to standard therapeutic approaches. Photodynamic therapy (PDT) is an underutilised cancer therapy with an increased potency and negligible side effects, and it is non-invasive compared to traditional treatment modalities. Three-dimensional multicellular tumour spheroids (MCTS) closely resemble in vivo avascular tumour features, allowing for the more efficient and precise screening of novel anticancer agents with various treatment combinations. In this study, we utilised A375 human melanoma spheroids to screen the phototoxic effect of zinc phthalocyanine tetrasulfonate (ZnPcS4) conjugated to gold nanoparticles (AuNP). The nanoconjugate was synthesised and characterised using ultraviolet-visible spectroscopy, a high-resolution transmission electron microscope (TEM), dynamic light scattering (DLS), and zeta potential (ZP). The phototoxicity of the nanoconjugate was tested on the A375 MCTS using PDT at a fluency of 10 J/cm2. After 24 h, the cellular responses were evaluated via microscopy, an MTT viability assay, an ATP luminescence assay, and cell death induction using annexin propidium iodide. The MTT viability assay demonstrated that the photoactivated ZnPcS4, at a concentration of 12.73 µM, caused an approximately 50% reduction in the cell viability of the spheroids. When conjugated to AuNPs, the latter significantly increased the cellular uptake and cytotoxicity in the melanoma spheroids via the induction of apoptosis. This novel Zinc Phthalocyanine Nanoconjugate shows promise as a more effective PDT treatment modality.